Lupeol and amphotericin B mediate synergistic anti-leishmanial immunomodulatory effects in Leishmania donovani-infected BALB/c mice. (January 2021) - Das, Antu; Jawed, Junaid Jibran; Das, Manash C.; Parveen, Shabina; Ghosh, Chinmoy; Majumdar, Subrata; Saha, Bhaskar; Bhattacharjee, Surajit
Abstract: Leishmania donovani, a protozoan parasite, inflicts the disease Visceral leishmaniasis (VL) Worldwide. The only orally bioavailable drug miltefosine is toxic, whereas liposomal amphotericin B (AmpB) is expensive. Lupeol, a triterpenoid from Sterculia villosa bark, was exhibited immunomodulatory and anti-leishmanial activity in experimental VL. Herein, we evaluated synergism between sub-optimum dose of AmpB and lupeol in anti-leishmanial and immunomodulatory effects in L. donovani- infected BALB/c mice. We observed that a combination of sub-optimum dose of lupeol and AmpB significantly reduced the hepatic and splenic parasitic burden accompanied by enhanced nitric oxide production, robust induction of Th1 cytokines (IL-12 and IFN-γ) but suppressed Th2 cytokine (IL-10 and TGF- β) production. The treatment with the lupeol-AmpB combination enhanced p38mitogen-activated protein kinase (p38MAPK), but reduced extracellular signal-related kinase (ERK-1/2), phosphorylation and up-regulated pro-inflammatory response. The present work thus indicates a lupeol-AmpB-mediated immunotherapeutic approach for eliminating the parasite-induced immunosuppression.